The role of the father's class in the prevention of pregnant women with chronic energy deficiency : Lessons learned from Ngemplak-1 Health Center - Hassanah, Aprilya (BKM Public Health and Community Medicine, 2021)
Objective: Chronic energy deficiency is a state of a person's nutritional status is in an unfavorable condition. Pregnant women who have arm circumference >23.5 cm are considered to have poor nutritional status and experience chronic energy deficiency. The role of fathers in supporting the preparation of pregnant women until delivery is very much needed. It is hoped that this can reduce the incidence of pregnant women with chronic energy deficiency. Content: One of the causes of pregnant women with chronic energy deficiency is the lack of support from the community, especially the family, specifically husband. In this case, the father's participation in supporting the mother's pregnancy is very needed. Husband's support plays an important role in determining the health status of the mother during pregnancy because a husband not just meet the need financially but pregnant women also need psychological and biological support with the result that the mother is expected to be emotionally stable during pregnancy, Nutritional needs during pregnancy are considered and fulfilled, be a standby husband when women needs. To support the role of the father during pregnancy and prepare for the birth of the mother is to by making “father class”. Procurement of "father class" is one of the innovations carried out at the Ngemplak 1 Health Center. This program also needs support from community leaders, one of which is the village. Cross-sectoral collaboration between puskesmas and villages can reduce the burden on puskesmas so that program implementation can be maximized. Implementation can be done at the village level and as one of the village programs and the health center becomes the resource person.